A Small Pulmonary Arteriovenous Malformation as a Cause of Recurrent Brain Embolism - Todo, Kenichi; Moriwaki, Hiroshi; Higashi, Masahiro; Kimura, Kohji; Naritomi, Hiroaki (American Journal of Neuroradiology, 2004)
Summary: We report a case of recurrent paradoxical brain embolism mediated through a small pulmonary arteriovenous malformation (PAVM) with a 1.8-mm-diameter feeding artery. In this case, the further recurrent stroke was prevented successfully by PAVM embolization. Although embolization therapy is currently recommended only for PAVMs with feeding arteries greater than 3 mm in diameter, the therapy may be needed also in the smaller PAVMs.